THE EVOLUTION OF SOCIAL INDICATORS DEVELOPED AT THE LEVEL OF THE EUROPEAN UNION AND THE NEED TO STIMULATE THE ACTIVITY OF SOCIAL ENTERPRISES - Daniela PIRVU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2014)
The current concerns related to the stimulation of the activities of social enterprises are connected with the current economic and social challenges, faced by the EU member countries. This paper presents the evolution of the social indicators developed at the level of the European Union, relative to the social objectives of the Europe 2020 Strategy.